Effect of Ultrasonic Intensity Treatment on the Physicochemical and Functional Properties of Coregonus peled Protamine - Feifei Wang; Dong Shu; Yabo Wei; Xin Guo; Pingping Liu; Xiaorong Deng; Yunfeng Zhao; Yongdong Lei; Jian Zhang (Foods)
As the most valuable protein in the sperm of testes tissues of Coregonus peled, Coregonus peled protamine (CPP) had a natural antibacterial and antiseptic effect, but its physicochemical properties and functions are easily affected by the ultrasound-assisted extraction process. In this study, ultrasound-assisted extraction of CPP was used to investigate the effects of different ultrasonic intensities (0, 3.03, 6.07, 9.10, 12.13, and 15.16 W/cm2) on the structural and functional properties of CPP. The results showed that at moderate ultrasonic intensity (9.10 W/cm2), the protein was the most successful, as it was subjected to cavitation shear and microjet by ultrasound, which resulted in changes in protein structure, moderate unfolding of peptide chains, and changes in the secondary and tertiary structures of CPP. SEM images confirmed the changes in the microstructure of CPP. Ultrasound oxidized the proteins to varying degrees with the highest sulfhydryl and carbonyl and surface hydrophobicity content at an ultrasonic intensity of 9.10 W/cm2. At the same time, the solubility, antimicrobial activity, and heparin binding of CPP were affected. It is worth mentioning that the ultrasonicated CPP exhibited a stronger heparin-binding capacity compared to the non-ultrasonicated CPP. In conclusion, 9.10 W/cm2 was determined as the optimal ultrasonic intensity parameter for this study. In conclusion, the incorporation of appropriate ultrasonic intensity in the acidic extraction process could help to improve the functional properties of CPP, and ultrasound-assisted protein extraction has emerged as a reliable technique capable of modifying the structure and function of CPP.